Predisposing Factors of Cerebral Edema in Pediatric Diabetic Ketoacidosis: A Systematic Review - Hedayat Jafari; Pooneh Dadashian; Javad Ghaffari; Daniel Zaman Far (Mazandaran University of Medical Sciences, 2022)
Background: Diabetic ketoacidosis (DKA) is not the most common acute complication of type 1 diabetes in children and adolescents, but the cerebral edema caused by it is the most common cause of death in children with DKA. Objectives: The purpose of this study was to systematically review the literature to describe the predisposing factors of cerebral edema in pediatric DKA. Methods: Six international databases of Wiley, Medline, Scopus, Web of Science, ProQuest, and Cochrane Library, and three domestic databases, including SID, Magiran, and Iranmedex were searched for relevant studies. Then, articles with inclusion criteria and related to the objectives of this study were reviewed. Results: These studies have identified several risk factors for cerebral edema, some of which are related to the severity of the disease on admission and some are related to treatment. Conclusions: Preventing DKA is the only reliable way to prevent cerebral edema until the causes of this life-threatening complication are fully understood.